Analysis of The Islamic Leadership, Islamic Work Ethics and Intellectual Intelligence on Employee Performance with Islamic Organization Culture as Moderated Variables - Wilson Candra; Naelati Tubastuvi; Suryo Budi Santoso; Eko Haryanto (Universitas Muhammadiyah Yogyakarta, 2022)
This study aims to determine the effect of Islamic leadership, Islamic work ethic, and intellectual intelligence on employee performance with Islamic organizational culture as a moderating variable. The sample selection in this study was carried out by purposive sampling. Collecting data using a questionnaire. Based on the criteria, 120 respondents became the samples. Respondents must meet requirements such as Islam, a bachelor’s degree, and have 3 years of experience in Islamic banking. Hypothesis analysis using SPSS. The analytical technique used in this study is multiple regression analysis or Moderate Regression Analysis (MRA) to examine the interaction between variables. The results of this study indicate that Islamic Leadership, Islamic Work Ethics and Intellectual Intelligence can affect employee performance. Then Organizational Culture is not able to moderate the influence of Islamic Leadership and Islamic Work Ethics on Employee Performance, but organizational culture is able to moderate Intellectual Intelligence on Employee Performance.